THE EFFECT OF PERMENAKER 151/2020 POLICY FOR INDONESIAN MIGRANT WORKERS IN ONLINE MEDIA NEWS - Siswatiningrum, Etik; Danuwijaya, Try (Journal of International Relations, 2023)
Throughout the May 2020-April 2021 period, online media often reported Covid-19 pandemic as a global health disaster. All news related to Covid-19 has high news value because of its broad impact on society. Indonesian Migrant Worker (PMI) are having transnational mobility, so that it has negative stigma as a carrier of the virus was colored the news. They became the headlines for several online media in Indonesia during the Covid-19 pandemic. Seeing the large number of Indonesian migrant workers exposed to COVID-19, the Minister of Manpower issued a policy that limits the sending of migrant workers abroad through Permenaker 151/2020. This study aims to understand how online media in Indonesia report PMI related to the Covid-19 pandemic and its impact on placement policies. A number of positive and negative reports about PMI amid the Covid-19 polemic were found on online media portals in Indonesia. There are three largest online media in Indonesia based on the order of Alexa Rank which is used as a research instrument. The four online media are okezone.com, tribunnews.com and kompas.com Online media coverage is able to construct the public in responding to this change in the policy of placing TKI. By using the index measurement method based on the selected keywords, it was found that the three online media reported negative and positive news about PMI. In the narrative of online media reporting always presents three different groups of sources, namely PMI, the government, and PMI monitoring organizations.